Toxic interaction between Th2 cytokines and Staphylococcus aureus in atopic dermatitis - Travers, Jeffrey B. (2014)
Patients with atopic dermatitis (AD) are commonly colonized/infected with Staphylococcus aureus, and this bacterium is known to worsen the dermatitis. In this issue, Brauweiler et al. demonstrate a newly discovered mechanism by which Th2 cytokines involved in AD augments the toxicity of the lytic staphylococcal protein alpha toxin. This review presents mechanisms by which Th2 cytokines may interact with S. aureus to the detriment of the dermatitis.